Can ecosystem services certification enhance brand competitiveness of certified products? - Wanggi Jaung; Putzel, L.; Naito, D. (Elsevier, 2019)
Many ecolabels support sustainable production and consumption related to ecosystem services and could be used as a basis to develop ecosystem services certification. To generate a price premium and attract buy-in from producers, such a certification would need to boost the brand equity of the certified product above the competition. This study tests the feasibility of such an effect by analyzing the brand equity of certified bottled water using a choice experiment with 529 households in Lombok, Indonesia. Our results revealed enhanced brand equity of certified bottles, indicating an impact of ecolabel logos used to represent certification. However, the enhancement neither exceeded brand equity of competing brands of bottled water, nor reflected different values associated with the ecolabel logos. These results imply challenges for certification uptake in a competitive market, a need for branding and marketing of certification, and the importance of brand-competitiveness analysis in price premium studies.